Learning in the Concept of Biographicity. An Andragogical Perspective - Joanna Golonka-Legut (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2016)
The willingness to understand the essence/character of the process of human learning has inspired researchers for years, provoking them to undertake a number of cognitive actions. One ought to notice, however, that in spite of the numerous conclusions of a definitional nature the questions pertaining to the very process of learning remain without unambiguous answers. The andragogues' thinking has for years focused upon the activity and the role of an individual in lifelong learning and the immediate relation between individual life experience, the learning process, and biography. Not only do the scholars notice the educational potential of individual life experience (learning in one's life), but they also see the value of reflection on biography, which becomes the source of biographical learning. The present paper constitutes a voice in the discussion on learning and biography. The presented information pertains to such subjects as: understanding biography in the andragogical perspective, the biographical learning process. The entirety of the deliberations in concluded with a reflection on the relationship between the learning process and biography.